Prediction of runoff, sediment yield and their quality using ANSWERS model at Batujai reservoir area, West Nusa Tenggara - Gatot Irianto; Hidayat Pawitan; . Soedarsono; H. Soewardjo (Forum Pasca Sarjana, 1993)
The possibility of ANSWERS model application for predicting runoff and sediment yield is discussed in this paper. Three types of rainfall duration (e.i. 6; 8 and 10 hours) with three amount of total rainfall of 100; 200 and 300 mm and two different systems consistink of four kinds of land use were used for simulating runoff and sediment yield. The result showed that the runoff initiation was identified at 189 minutes from the start of rainfall when the amount of rainfall total was 200 mm with 8 hour duration (about 0.0001 inch/hour). The initial sediment yield was shown to be about 0.45 kg at 188 minutes from the begining of rainfall when rainfall total w+ 300 mm with 6 hour duration. Actual runoff and maximum sediment yield were recorded about 0.0017 inchlhour and 12.000 kg respectively. The land use which were considered as potential for erosion protection were mixed gardpn and wet rice. The considered land use would reduce runoff and sediment yield about 50% than traditional land use. The type of output indicates that ANSWERS model is promising for predicting runoff and sediment yield.